1996
DOI: 10.1002/(sici)1099-0720(199602)10:1<1::aid-acp354>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Children as witnesses: A comparison of lineup versus showup identification methods

Abstract: The goal of this study was to compare children's and adults eyewitness identification accuracy when presented with an array of possible suspects (‘lineup’) versus one suspect (‘showup’). Kindergarten children and adults were shown a slide show of a staged theft and subsequently asked whether, of the photo or photos shown them, the perpetrator was present or not. Children were more likely than adults to identify the perpetrator correctly when that suspect was present in the lineup or showup. Children were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 25 publications
5
60
1
1
Order By: Relevance
“…Also, even the youngest of child witnesses are capable of accurately reporting the behaviour of others (Ceci et al 1998). Regarding verbal recall (which may contain descriptive details), Dekle et al (1996) found that compared to adults, children's free recall is less complete (but equally accurate). When children are allowed to recall information freely or through the use of general questions, even very young children can produce material that is as accurate as that given by adults (Hutche-son et al 1995).…”
Section: Children's Statements and Person Descriptionssupporting
confidence: 91%
See 1 more Smart Citation
“…Also, even the youngest of child witnesses are capable of accurately reporting the behaviour of others (Ceci et al 1998). Regarding verbal recall (which may contain descriptive details), Dekle et al (1996) found that compared to adults, children's free recall is less complete (but equally accurate). When children are allowed to recall information freely or through the use of general questions, even very young children can produce material that is as accurate as that given by adults (Hutche-son et al 1995).…”
Section: Children's Statements and Person Descriptionssupporting
confidence: 91%
“…Children's free recall usually contains few information units (Dekle et al 1996). However, when children are allowed to recall information freely or through the use of general questions, even very young children can produce material which is highly accurate (Hutcheson et al 1995 Developmentally it is typically more efficient to ask children general questions, because specific questions or difficult explanations can confuse children and result in increased numbers of false details.…”
Section: Questioning Methods With Childrenmentioning
confidence: 95%
“…a lineup containing only innocent persons), children are significantly more likely than adults to incorrectly identify someone as the perpetrator (Beal, Schmitt, & Dekle, 1995;Davies, 1996;Dekle, Beal, Elliott, & Huneycutt, 1996;Parker & Carranza, 1989;Parker & Ryan, 1993;Pozzulo & Balfour, 2006;Pozzulo & Dempsey, 2006). By adolescence (10-14 years), some research indicates that identification accuracy in target-absent lineups reaches adult levels Pozzulo & Warren, 2003, Experiment 2; for reviews, see, Havard, 2013: Pozzulo, 2007Pozzulo & Lindsay, 1998).…”
Section: Receiver Operating Characteristic Analysis Of Age-related Chmentioning
confidence: 99%
“…Children may also feel more social pressure to positively identify a face and feel greater reluctance to declare uncertainty compared to adults (Beal, et al, 1995;King & Yuille, 1987;Ricci, Beal, & Dekle, 1996). Children may also be less aware of the consequences of making a false identification (Brewer, Weber, & Semmler, 2005;Dekle, et al, 1996;Spring, Saltzstein, & Peach, 2013). Other researchers have proposed that memory sensitivity and response bias differ with age.…”
Section: Receiver Operating Characteristic Analysis Of Age-related Chmentioning
confidence: 99%
“…This analysis of criterion placement in simultaneous and sequential lineups may also apply to other results not included in our analyses. For example, some have suggested that sequential lineups are not advisable for child witnesses (Pozzulo & Lindsay, 1998), who may also tend to have lower decision criteria than do adult witnesses (see Dekle, Beal, Elliot, & Huneycutt, 1996).…”
Section: Summary and Synthesismentioning
confidence: 99%